Credibility without rules? : monetary frameworks in the post-Bretton Woods era - Cottarelli, Carlo; Giannini, Curzio; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper is the story of the search for a better trade-off between flexibility and credibility undertaken by authorities around the world in the last 25 years. It provides detailed information on how monetary frameworks - that is the set of announced rules and institutions affecting monetary policy - evolved in 100 countries, examining the forces that molded such evolution and focusing on how developments in economic theory affected the choices of policy-makers.
"December 1997."
Includes bibliographical references: p. 85-92.
lje 21/07/2016
Loans
Keywords: Monetary policy; Banks and banking, Central